Influence of training and development, employee performance on job satisfaction among staff in School of Technology Management and Logistics (STML, UUM) - Liza, Othman (2017)
This paper explored on the influence of training and development, employee performance on job satisfaction among staff of School of Technology Management and Logistics (STML). The purpose of this research paper is to identify the influence of training & development program and employee performance on job satisfaction among university academic and administrative staff in STML. Quantitative research method of primary source was utilized to collect the data from 69 academic and administrative respondents. The context of this study is on Universiti Utara Malaysia, Sintok, Kedah (UUM) in the northern region of Malaysia. Seven Likert scale was used to measure the degree of training & development and employee performance on job satisfaction. Progression analysis was used to analyse and test the hypothesis. The result found that training & development and employee performance positively influence on job satisfaction, and there is a significant relationship between training & development, employee performance and job satisfaction. It also established that training & development and employee performance is an effective and supportive key factor to organization and employee success. This paper presents significant theoretical contribution for academic knowledge purpose and practical contributions for practitioners.